Japanese picture dictionary : learn 1,500 Japanese words and phrases - Timothy G. Stout (Tokyo : Tuttle Publishing, 2018)
Containing culture-specific Japanese words and images not found in other picture dictionaries, Stout provides the Japanese script forms along with Romanized pronunciations and English definitions. The words are grouped into 38 themes or topics, each with 25-45 words, and several sentences, covering all the essential vocabulary--including the 1,500 critical Japanese words and sentences that students need to know to pass the AP Japanese Language and Culture Exam and the JLPT proficiency exams. Includes over 600 color photographs and an English-Japanese index
Keywords: Dictionaries; LANGUAGE ARTS & DISCIPLINES / Study & Teaching; FOREIGN LANGUAGE STUDY / Multi-Language Dictionaries; English language